Alterations of the Primary Cilia Gene SPAG17 and SOX9 Locus Noncoding RNAs Identified by RNA‐Sequencing Analysis in Patients With Systemic Sclerosis. Issue 1 (29th November 2022) - Roberson, Elisha D. O.; Carns, Mary; Cao, Li; Aren, Kathleen; Goldberg, Isaac A.; Morales‐Heil, David J.; Korman, Benjamin D.; Atkinson, John P.; Varga, John
Abstract : Objective: Systemic sclerosis (SSc) is characterized by immune activation, vasculopathy, and unresolving fibrosis in the skin, lungs, and other organs. We performed RNA‐sequencing analysis on skin biopsy samples and peripheral blood mononuclear cells (PBMCs) from SSc patients and unaffected controls to better understand the pathogenesis of SSc. Methods: We analyzed these data 1) to test for case/control differences and 2) to identify genes whose expression levels correlate with SSc severity as measured by local skin score, modified Rodnan skin thickness score (MRSS), forced vital capacity (FVC), or diffusing capacity for carbon monoxide (DLco ). Results: We found that PBMCs from SSc patients showed a strong type I interferon signature. This signal was found to be replicated in the skin, with additional signals for increased extracellular matrix (ECM) genes, classical complement pathway activation, and the presence of B cells. Notably, we observed a marked decrease in the expression of SPAG17, a cilia component, in SSc skin. We identified genes that correlated with the MRSS, DLco, and FVC in SSc PBMCs and skin using weighted gene coexpression network analysis. These genes were largely distinct from the case/control differentially expressed genes. In PBMCs, type I interferon signatures negatively correlated with the DLco . In SSc skin, ECM gene expression positively correlated with the MRSS. Network analysis of SSc skin genes that correlated with clinical features identified the noncoding RNAs SOX9‐AS1 and ROCR, both near the SOX9 locus, as highly connected, "hub‐like" genes in the network. Conclusion: These results identify noncoding RNAs and SPAG17 as novel factors potentially implicated in the pathogenesis of SSc.